The use of whole genome sequencing to study young patients with 100+ adenomas of the colon - Tsukanov, Aleksey S.; Achkasov, Sergey I.; Loginova, Anna N.; Shubin, Vitaly P.; Pikunov, Dmitry Y.; Chekanov, Nikolay N.; Salomatina, Anastasiya S.; Severinov, Konstantin V. (Frontiers in Oncology, 2025)
ObjectiveAdenomatous polyposis syndrome (APS) is a rare hereditary disease characterized by the development of multiple (more than 20) adenomas of the colon with a high-risk of malignant transformation without surgical treatment. The most aggressive form of APS, with >100 polyps before the age of 45 years, is mostly caused by germline pathogenic variants in the APC gene but patients with germline variants in the MUTYH and, very rarely, in the SMAD4 and BMPR1A genes were also reported. Routine molecular testing methods, such as Sanger sequencing, multiplex ligation-dependent probe amplification (MLPA) or multigene NGS panels, may fail to detect pathogenic variants in non-coding regions.Patients and methodsDNA from blood samples of 10 patients (with age of APS manifestation between 15 and 45 years) with over 100 adenomatous colonic polyps identified by endoscopic examination was subjected to whole genome sequencing (WGS). Prior genetic testing did not detect any germline pathogenic variants in the APC and MUTYH coding exons in these patients.ResultsPathogenic and likely pathogenic germline variants in non-coding regions of genes were identified in 3 patients. Two unrelated patients had the same c.-190G>A (rs879253785) in the 1B promoter of the APC gene (NM_001127511.3), while the third patient had a c.-152-2A>G variant in the BMPR1A gene (NM_004329.3). Using standard NGS panels or whole exome sequencing (WES) would not have detected these variants.ConclusionOur results demonstrate that WGS is a useful genetic testing method for young patients with over 100 adenomatous colonic polyps, when routine DNA diagnostic methods fail to establish the genetic cause of the disease.